Mechanically robust 3D hierarchical electrode via one-step electro-codeposition towards molecular coupling for high-performance flexible supercapacitors. (January 2020) - Li, Weizhao; Zu, Xihong; Zeng, Yanxian; Zhang, Leyuan; Tang, Zilun; Yi, Guobin; Chen, Zihan; Lin, Wenjing; Lin, Xiaofeng; Zhou, Huankai; Xiao, Jing; Deng, Yulin
Abstract: Flexible solid-state supercapacitor (FSSC) is one of the most promising energy devices for wearable and portable electronics due to the advantages of high energy/power density, outstanding flexibility, good mutual compatibility and good safety. However, the serious performance decay of FSSCs caused by the structure and shape deformation of the devices is still a remaining challenge. Here, we report a high-performance FSSC with well-designed 3D Co3 O4 nanowires @ MnO2 -PPy hybrid nanoflake electrode made by a facile and effective one-step electro-codeposition method. To form a 3D skeleton, Co3 O4 nanowires are vertically grown on carbon fibers, which improves the surface area and mass loading of pseudocapacitive materials. More importantly, it is also beneficial to avoid structure collapse during the bending, folding or twisting. Furthermore, MnO2 -PPy nanoflakes grown on Co3 O4 nanowires are capable to achieve the ultra-high surface area, fast electron/ion transport pathways and high utilization efficiency of the active materials. The specific capacitance of the constructed FSSC is as high as 215 F g −1 at the current density of 0.5 A g −1 . The high energy density (41.3 Wh kg −1 ) and power density (4348 W kg −1 ) with a high capacitance retention of 93.0% after 1000 bending and twisting cycles are also achieved, indicating that it has a great potential for practical application in wearable and portable electronics. Graphical abstract: This paper reports a high-performance FSSC with well-designed 3D Co3 O4 nanowires @ MnO2 -PPy hybrid nanoflake electrode made by a facile and effective one-step electro-codeposition method. The MnO2 -PPy nanoflake shell is homogeneously composited of highly capacitive MnO2 and conductive PPy at the molecular level, generating a strong molecular coupling which enormously improves the electron transfer efficiency and utilization efficiency of MnO2 . Image 1 Highlights: 3D hierarchical electrode was designed for flexible all-solid-state supercapacitors. MnO2 -PPy hybrid nanoflake shells towards molecular coupling were fabricated. The capacitance retention was above 93.0% after 1000 cycle deformation. The wearable all-solid-state supercapacitors can power numbers of LEDs.